2023
DOI: 10.3847/1538-4357/acb7de
|View full text |Cite
|
Sign up to set email alerts
|

New Determination of the 12C(α, γ)16O Reaction Rate and Its Impact on the Black-hole Mass Gap

Abstract: We present a precise measurement of the asymptotic normalization coefficient (ANC) for the 16O ground state (GS) through the 12C(11B, 7Li)16O transfer reaction using the Quadrupole‐3‐Dipole (Q3D) magnetic spectrograph. The present work sheds light on the existing discrepancy of more than 2 orders of magnitude between the previously reported GS ANC values. This ANC is believed to have a strong effect on the 12C(α, γ)16O reaction rate by constraining the external capture to the 16O ground state, which can interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Notably, Kunz et al (2002) considerably lowered the nominal rate compared to the NACRE compilation. Shen et al (2023) also recently found a rate that was significantly higher than the values of Xu et al (2013) anddeBoer et al (2017). The value of the 12 C(α, γ) 16 O rate is therefore still uncertain.…”
Section: Nuclear Reactions In Rc Starsmentioning
confidence: 74%
“…Notably, Kunz et al (2002) considerably lowered the nominal rate compared to the NACRE compilation. Shen et al (2023) also recently found a rate that was significantly higher than the values of Xu et al (2013) anddeBoer et al (2017). The value of the 12 C(α, γ) 16 O rate is therefore still uncertain.…”
Section: Nuclear Reactions In Rc Starsmentioning
confidence: 74%
“…This feature has often been attributed to the pulsational pairinstability pileup (e.g., Talbot & Thrane 2018;Farr et al 2019;Stevenson et al 2019), which would agree with our result presented here. However, recent updates of the tabulated 12 C(α, γ) 16 O reaction rates have pushed the lower boundary of PPISN, and the corresponding expected location of a pileup in the remnant mass distribution, to higher masses (Farmer et al 2020;Farag et al 2022;Mehta et al 2022;Hendriks et al 2023;Shen et al 2023). More updated prescriptions would therefore not result in a PPISN, but in direct core-collapse supernova.…”
Section: Binary Black Hole Formation and Potential Pairinstability Pu...mentioning
confidence: 99%
“…This is a unique process, setting stringent conditions for helium ignition. The 3α process is followed by the α-capture reaction 12 C(α, γ) 16 O, converting the 12 C into 16 O (deBoer et al 2017;Mehta et al 2022;Shen et al 2023). These two isotopes are the principal products of helium burning.…”
Section: Introductionmentioning
confidence: 99%